Sharī'ah scrutiny of Islamic Banks' Financial Compensation Fund in Bangladesh: Governance principles in the COVID-19 perspective - Abdullah Masum; Shariful S M Islam (Islamic Economic Studies (IES), 2022)
Purpose The purpose of this study is to critically analyze the Financial Compensation Funds being accumulated by Islamic Banks of Bangladesh in credit-based transactions. In this connection, due to the evolved liquidity crisis amidst the COVID-19, industry opinions are observed that suggest including the compensations or the donation funds directly into the bank's income account. But the Sharī'ah does not permit it. Such alternative proposals of using compensation or donation fund during crises are scrutinized under Sharī'ah principles to come to a logical conclusion. Design/methodology/approach The approach followed in the study is textual and discourse analysis through descriptions of ideal Sharī'ah-compliant methods for handling late payment of credit and comparison with the industry practices. Findings It is observed that there are conceptual gaps in the industry as is reflected in the Islamic Banking Guideline of Bangladesh. The funds collected from the debtor due to late payment are named as compensation (Ta'wid) whereas the nature of the transaction is a donation (Tabarru'). The misconception can lead to various Sharī'ah non-compliant activities later with the funds. The proposals brought out in the industry to use such compensation/donation funds during a crisis are a consequence of this. The proposals of using such funds for banks' purposes in any situation are not supported by Sharī'ah principles and are against the Islamic banking philosophy. Originality/value The study is very relevant to the current crisis of COVID-19 in the domestic Islamic Banking Industry and also instrumental for the future guidance to stick to the Sharī'ah principles in managing compensation or donation funds by the Islamic Banks.
Keywords: G20; G21; G28; 330; Gharamah; Al-Iltizam bi-al-Tabarru'; Penalty clause; Islamic bank; Bangladesh